Effect of Mesona chinensis polysaccharide on pasting, rheological and structural properties of corn starches varying in amylose contents. (15th February 2020) - Luo, Yu; Shen, Mingyue; Li, Enpeng; Xiao, Yuehuan; Wen, Huiliang; Ren, Yanming; Xie, Jianhua
Highlights: MCP increased the pasting viscosity of corn starch-MCP blended systems. The amylose content affects the structural properties of blended systems. MCP inhibited the dissolution of NS and the swelling of WS. Corn starch-MCP systems exhibited a pseudoplastic and shear-thinning behavior. Abstract: Waxy corn starch (WS), normal corn starch (NS), and high amylose corn starch (HS) were used to investigate the effect of Mesona chinensis polysaccharide (MCP) on pasting, rheological, and textual properties of corn starches. Corn starches (6 %, w/v)-MCP (0.05 %, 0.1 %, 0.2 %, 0.3 %, and 0.5 %, w/v) blended systems were used. The pasting viscosity of samples increased after adding MCP, and the improvement effect was most noticeable in WS-MCP system. Meanwhile, MCP can significantly promote the gelatinization and strengthen viscoelasticity of HS-MCP system. MCP inhibited the dissolution of NS and the swelling of WS, while promote the dissolution of HS and WS, as well as the swelling of NS and HS. Furthermore, gelatinization treatment decreased the crystallinity of samples, while high concentration of MCP slightly increased the crystallinity. MCP could promote the formation of a more ordered structure of blended systems, especially for WS-MCP system.